Women in Community Rubber Plantations in Panca Tunggal Village, Sungai Lilin District - Muhamad Idris; Murjainah; Mirna Taufik; Agustina, Ema; Nur Syafrudin; Gassar, Abdo Abdullah Ahmed (Indonesian Journal of Advanced Research, 2024)
Panca Tunggal Village, Sungai Lilin subdistrict, Musi Banyuasin district is one of the rubber plantation areas. This research aims to describe and describe the phenomenon of women rubber farmers in smallholder industrial rubber plantations in Panca Tunggal village, Sungai Lilin sub-district, Musi Banyuasin district. The research method used is a descriptive method, with data collection in the form of observations and questionnaires. The analysis used uses the Miles Huberman model, namely reduction, presentation and conclusion. The results of the research show that the education level of female rubber farmers is lowest at the high school level. The income earned by women rubber farmers is used to meet the educational needs of their children. Meeting the needs of the families of women rubber farmers depends on the price of rubber.